ANALYSIS OF THE PLANT SPECIES USED FOR TECHNICAL PURPOSES IN CHECHNYA - Musa A. Taysumov; Mukhadin U. Umarov; Marzhan A.-M. Astamirova; Aminat S. Abdurzakova; Raisa S. Magomadova; Satsita A. Israilova; Kheda L. Khalidova; Birlant A. Khasueva (Юг России: экология, развитие)
Aim. The aim of the research is to define the species composition of technical plants, to conduct its comprehensive analysis and identify useful properties of wild species of Chechnya for enriching the range of plants used for technical purposes. Methods. The object of the study was the flora and spatial localization of certain types of technical plants on the territory of Chechnya and adjacent territories. The material for the study was obtained as a result of observations in nature and collection of herbarium material during expeditionary researches from 2010 to 2017. Discussion. The article lists dyeing, essential oil-bearing, tannic, tar-bearing plants of the flora of Chechnya and adjacent territories. The main woodraw plants that provide valuable wood are also given special attention in the research; the qualitative properties of various woods and their intended use are briefly described. Are also descried many arboreal and herbaceous species which are widely used or are promising for tanning leather, fabrics, as well as species for obtaining essential oils and aromatic substances suitable for the use in liquor and vodka production, confectionery and other industries. Conclusion. The availability of large reserves of raw technical crops in the republics of the North Caucasus makes them very promising for industrial use. The study of the properties of biologically active substances, establishment of their structure, and creation of valuable herbal preparations on their basis is of great practical importance. On the territory of the Chechen Republic we have identified 157 types of technical plants belonging to 74 genera and 35 families. The problem of preserving the species diversity of valuable, economically useful, including technical plants in culture, becomes especially urgent in connection with the expansion of the use of new species as sources of biological substances.